Hemadsorption for removal of ticagrelor and direct oral anticoagulants in cardiac surgery. (1st February 2022) - Jackson, Robyn; Trus, Ryan Matthew; El-Diasty, Mohammad
ABSTRACT: Introduction: Cardiac patients on antiplatelets or oral anticoagulation undergoing emergent cardiac surgery without appropriate washout periods are at increased risk for developing perioperative bleeding. CytoSorb is a commercially available hemadsorption adsorber that can simultaneously remove a wide range of substances including ticagrelor, and direct oral anticoagulants (DOACs). Areas covered: Although CytoSorb has been used to remove various protein-bound substances, this review will specifically evaluate and review current evidence for applying CytoSorb in removing ticagrelor and DOACs using four in vitro studies, three case reports, one retrospective study and two cost analysis studies. Based on limited evidence, CytoSorb may be effective in reducing perioperative bleeding by reducing chest tube output, blood product transfusions, and re-thoracotomy rates. CytoSorb can also reduce length of intensive care unit (ICU) and hospital stay. Although, CytoSorb has an initial upfront cost, it was proven to be cost-effective due to potential health resource savings on both short- and long-term projections. Expert Commentary: CytoSorb provides a novel strategy to remove ticagrelor and DOACs in patients requiring emergency cardiac surgery. Although promising results, more solid evidence is required to establish its clinical effectiveness in reducing perioperative bleeding, bleeding-related complications, mortality, and finally, its overall safety.